1979
DOI: 10.1007/bf00234852
|View full text |Cite
|
Sign up to set email alerts
|

Classification of human placental villi

Abstract: The classification of human placental villi was reviewed on the basis of material prepared by means of special methods. The material from in situ normal-term placentae was biopsied by aspiration into glutaraldehyde. The classification was made on the basis of light-microscopic observations of semithin sections, reconstructions from serial sections, and scanning-electron micrographs. The peripheral villous tree is roughly divided into stem (ramuli), intermediate and terminal villi. The intermediate villi may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 11 publications
4
43
0
Order By: Relevance
“…Generally, placental villi are grouped into stem and terminal villi (Kaufmann et al 1979). The terminal villi are the final branches of the villous tree through which the fetus establishes contact with the maternal circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, placental villi are grouped into stem and terminal villi (Kaufmann et al 1979). The terminal villi are the final branches of the villous tree through which the fetus establishes contact with the maternal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The regional structural variations of the placenta could probably be evaluated in more accurate terms if they were subjected the morphometric evaluations (Wigglesworth 1969;Bjork and Persson 1984). Therefore, the same portion of the placenta is used for Kaufmann et al 1979). We have found that in diabetic placentae the diameter of terminal villi is significantly smaller, despite tight metabolic control of the mothers' diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…The chorionic villi increase in num ber and length and decrease in diameter; the villous tree becomes progressively more arborized with stem, inter mediate and terminal chorionic villi [12,17,18]. During gestation there is also a morphological modification of the different components of the placental villi: a progres sive disappearance of cytotrophoblastic cells, a syncytio trophoblastic thinning associated with a thickening of the villous stroma and a decrease in mesenchymal cells [19], Some authors considered these morphostructural modulations as placental ageing, while more rational studies define them as maturation and differentiation aspects of the maternal-fetal contact surface [1].…”
Section: Discussionmentioning
confidence: 99%
“…Semithin cross sections of the villi, about 1 11m thick, were stained with toluidine blue. The villous cross sections were classified according to stromal structure following the classification of Kaufmann et al (1979). The vessel types were identified as far as possible in semithin sections, following the classification of Rhodin (1967Rhodin ( , 1968Rhodin ( , 1974.…”
Section: Methodsmentioning
confidence: 99%